1996
DOI: 10.1007/bf00419460
|View full text |Cite
|
Sign up to set email alerts
|

Mushroom nutriceuticals

Abstract: There has been a recent upsurge of interest in mushrooms as a source of biological active compounds of medicinal value including anti-cancer, anti-viral, immunopotentiating, hypocholesterolaemic and hepatoprotective agents. This new class of compounds, termed 'mushroom nutriceuticals', are extractable from either the fungal mycelium or fruiting body and represent an important component of the expanding mushroom biotechnology industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
170
0
11

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(184 citation statements)
references
References 7 publications
3
170
0
11
Order By: Relevance
“…Protein is an important constituent of dry matter of mushrooms (Aletor, 1995;Alofe et al, 1995;Fasidi and Kadiri, 1990;Florczak and Lasota, 1995;Zrodlowski, 1995;Chang and Buswell, 1996). Lintzel (1941) reported the digestibility of mushroom protein to be as high as 72 to 83%.…”
Section: Proteinsmentioning
confidence: 99%
“…Protein is an important constituent of dry matter of mushrooms (Aletor, 1995;Alofe et al, 1995;Fasidi and Kadiri, 1990;Florczak and Lasota, 1995;Zrodlowski, 1995;Chang and Buswell, 1996). Lintzel (1941) reported the digestibility of mushroom protein to be as high as 72 to 83%.…”
Section: Proteinsmentioning
confidence: 99%
“…For thousands of years fungi have been recognised as nutritious, highly palatable functional foods in many societies and are now accepted as a valuable source for the development of medicines and nutraceuticals (Chang & Buswell, 1996;Wasser, 2002). Pharmacological and medicinal studies of fungi have shown that the Basidiomycete and Ascomycete divisions are an immense source of biologically active components, yet less than ten percent of all species have been described and even less have been tested for therapeutic significance (Blackwell, 2011;Lindequist, Niedermeyer, & Julich, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Protein tends to be present in an easily digested form in mushrooms (Chang and Buswell, 1996;Chang and Mshigeni, 2001). Mushroom protein contains all the essential amino acids needed in the human diet and are especially rich in lysine and leucine which are lacking in most staple cereal foods (Chang and Buswell, 1996;Sadler, 2003). Evaluation of crude protein in case of C. indica mutants indicated a range of 9.28-15.60% protein.…”
Section: Resultsmentioning
confidence: 99%